Detection of kala-azar among children in Al Muthanna province - Zahraa Abd ALHammza Abbass (Al-Qadisiyah Journal of Pure Science, 2017)
The current study was conducted in Al Muthanna province to detect the Kala-azar infection among children. Result showed that the total infection rate of kala- azar was 17.75%. The age showed the higher infection rate in age (1- <2 ) year and the lower infection rate in age ( 4 – 5 ) year ,The difference was statistically significant (p<0.01).Result appear higher infection rate in male 55.26% than female 44.37% , There is no significant difference (p<0.01). distribution of kala- azar by region showed the infection rate in rural area 65.78% is higher from urban area 34.21% , The difference was significant between rural and urban area (p<0.01). prevalence kala azar by months of year appear that higher infection rate in march 35% then November 27.27% then January 26.66% and decrees infection in July, The difference was significant among month year (p<0.01).